2021
DOI: 10.1111/febs.16215
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal protein AstaP is a potent carotenoid solubilizer and delivery module with a broad carotenoid binding repertoire

Abstract: Carotenoids are lipophilic substances with many biological functions, from coloration to photoprotection. Being potent antioxidants, carotenoids have multiple biomedical applications, including the treatment of neurodegenerative disorders and retina degeneration. Nevertheless, the delivery of carotenoids is substantially limited by their poor solubility in the aqueous phase. Natural water-soluble carotenoproteins can facilitate this task, necessitating studies on their ability to uptake and deliver carotenoids… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 87 publications
(222 reference statements)
0
22
1
Order By: Relevance
“…Considering the presumable domain structure of this protein (Fig. 1b ) and assuming almost equivalent binding of xanthophylls AXT, CAN, and ZEA 15 , we prepared AstaPo1 mutants lacking either the N-terminal region, or the C-terminal region, or both, and selected to produce them in ZEA-synthesizing E. coli cells, which were known to yield stable ZEA-bound non-truncated AstaPo1 15 . Analytical size-exclusion chromatography (SEC) with continuous absorbance spectrum detection confirmed that truncations lead to a stepwise reduction of the protein monomer size (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the presumable domain structure of this protein (Fig. 1b ) and assuming almost equivalent binding of xanthophylls AXT, CAN, and ZEA 15 , we prepared AstaPo1 mutants lacking either the N-terminal region, or the C-terminal region, or both, and selected to produce them in ZEA-synthesizing E. coli cells, which were known to yield stable ZEA-bound non-truncated AstaPo1 15 . Analytical size-exclusion chromatography (SEC) with continuous absorbance spectrum detection confirmed that truncations lead to a stepwise reduction of the protein monomer size (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While the preprotein contained a predicted signal peptide for secretion, it was accumulated on the cell periphery in response to hyperinsolation and osmotic stress (often associated with drought conditions), to perform a photoprotective role, presumably, via direct quenching of reactive oxygen species (ROS) and also via high-energy light filtering effects 13 . Unlike the cyanobacterial photosensory Orange Carotenoid Protein (OCP) 14 , AstaP did not undergo a photo-induced transformation even after intense illumination 15 . Several orthologs of AstaP have been isolated from Scenedesmus sp.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…PCC 7120 (hereinafter AnaCTDH protein) can uptake carotenoids (echinenone and canthaxanthin) from membranes of carotenoid-producing E. coli strains [ 21 , 22 ] and serve as an effective machinery for delivery of ketocarotenoids into cell membranes [ 23 ]. Exploitation of carotenoid-producing strains allowed to reconstitute holoforms of the ~20 kDa microalgal Astaxanthin-binding Protein (AstaP), which can accommodate several carotenoid types (astaxanthin, canthaxanthin, zeaxanthin, lutein and β-carotene) and transfer them to liposomes and apoforms of unrelated carotenoproteins from cyanobacteria [ 24 ]. In addition, it is known that the color of cocoons in silkworm Bombyx mori originates from carotenoids that are delivered by the intracellular ~30 kDa Carotenoid-Binding Protein (CBP) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%